Acute arterial occlusion after total knee arthroplasty: a case report. Issue 8 (11th July 2017) - Inomata, Kei; Sekiya, Ichiro; Otabe, Koji; Nakamura, Tomomasa; Horie, Masafumi; Koga, Hideyuki; Watanabe, Toshifumi; Muneta, Takeshi
Key Clinical Message: Popliteal artery occlusion after total knee arthroplasty is rare (0.03–0.17%) but can lead to amputation if overlooked. We should carefully assess vascular patency by Doppler ultrasound and ankle brachial pressure index (ABPI) measurement before and after total knee arthroplasty (TKA) operation. Abstract : Popliteal artery occlusion after total knee arthroplasty is rare (0.03–0.17%) but can lead to amputation if overlooked. We should carefully assess vascular patency by Doppler ultrasound and ankle brachial pressure index (ABPI) measurement before and after total knee arthroplasty (TKA) operation.